2011
DOI: 10.1121/1.3632091
|View full text |Cite
|
Sign up to set email alerts
|

Resonances and wave propagation velocity in the subglottal airways

Abstract: Previous studies of subglottal resonances have reported findings based on relatively few subjects, and the relations between these resonances, subglottal anatomy, and models of subglottal acoustics are not well understood. In this study, accelerometer signals of subglottal acoustics recorded during sustained [a:] vowels of 50 adult native speakers (25 males, 25 females) of American English were analyzed. The study confirms that a simple uniform tube model of subglottal airways, closed at the glottis and open a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Considered separately for males and females, Sg1 is not strongly correlated with Sg2 or Sg3 (0.27 < r < 0.58), but Sg2 is strongly correlated with Sg3 (r > 0.73). The poor correlations involving Sg1 are presumably due to the effects of the subglottal tissue resonance, which was shown to be in the vicinity of Sg1 (Lulich et al, 2011a) and which may variably affect the Sg1 frequency (without altering the Sg2 and Sg3 frequencies) depending on the mechanical properties of the tissue and the proximity of Sg1 to the tissue resonance. The strong correlation between Sg2 and Sg3 was noted before (Lulich et al, 2011a) and, together with the fact that the mean ratio between Sg3 and Sg2 (1.62) is roughly equal to the expected relation 5/3, is evidence that at frequencies far from the tissue resonance the subglottal system behaves like an equivalent uniform tube closed at the glottal end and open at the distal end.…”
Section: Femalesmentioning
confidence: 99%
See 3 more Smart Citations
“…Considered separately for males and females, Sg1 is not strongly correlated with Sg2 or Sg3 (0.27 < r < 0.58), but Sg2 is strongly correlated with Sg3 (r > 0.73). The poor correlations involving Sg1 are presumably due to the effects of the subglottal tissue resonance, which was shown to be in the vicinity of Sg1 (Lulich et al, 2011a) and which may variably affect the Sg1 frequency (without altering the Sg2 and Sg3 frequencies) depending on the mechanical properties of the tissue and the proximity of Sg1 to the tissue resonance. The strong correlation between Sg2 and Sg3 was noted before (Lulich et al, 2011a) and, together with the fact that the mean ratio between Sg3 and Sg2 (1.62) is roughly equal to the expected relation 5/3, is evidence that at frequencies far from the tissue resonance the subglottal system behaves like an equivalent uniform tube closed at the glottal end and open at the distal end.…”
Section: Femalesmentioning
confidence: 99%
“…For Sg1, the wave propagation velocity is increased to c ¼ c w ¼ 46 586 cm/s as a result of the nearby wall tissue resonance (Lulich et al, 2011a).…”
Section: Height and Age Dependence Of Subglottal Resonancesmentioning
confidence: 99%
See 2 more Smart Citations
“…1) uses a piece-wise linear function to map the first three SGRs -Sg1, Sg2 and Sg3 -of a target speaker (subscript t) to the first three SGRs of a reference speaker (subscript r). Since Sg2 and Sg3 are not necessarily integer multiples of Sg1 [14], SGR warping results in frequency-dependent scaling. As Fant's studies on vowel normalization have shown [15], speaker variability can be best minimized using a combination of frequency-independent and frequency-dependent scaling.…”
Section: Vtln Versus Sgr Warpingmentioning
confidence: 99%